Colonialism and race in Luso-Hispanic literature - Branche, Jerome (University of Missouri Press, 2006)
"Branche examines a wide variety of Latin American literature and discourse to show the extent and range of racist sentiments throughout the culture. He argues that racism in the modern period (1415-1948) was a tool used to advance Spanish and Portuguese expansion, colonial enterprise, and the international development of capitalism"--Provided by publisher